PHONETIC EXPRESSIVE MEANS: ALLITERATION, ONOMATOPOEIA - Axmadjonova Oydinoy,; G’ofurova S. M., (TADQIQOTLAR, 2026)
Abstract:  This  article  examines  the  role  of  phonetic  expressive  means, particularly alliteration and onomatopoeia, in the stylistic organization of language and literary texts. Phonetic devices function as important tools that enhance the emotional, aesthetic, and imaginative qualities of speech through the deliberate arrangement of sounds. The article focuses on the linguistic nature of alliteration as the repetition of similar  consonant  sounds  in  neighboring  words,  which  contributes  to  rhythm, musicality, and emphasis within a text. It also analyzes onomatopoeia as the imitation of natural or environmental sounds through language, allowing writers to create vivid auditory imagery and intensify the sensory perception of the reader. Special attention is  given  to  the  stylistic  functions  of  these  phonetic  expressive  means  in  literary discourse, where they help to convey mood, strengthen semantic content, and produce a  stronger  emotional  impact.  The  study  demonstrates  that  alliteration  and onomatopoeia are not merely decorative elements of language but significant stylistic devices that enrich the expressive potential of speech and contribute to the artistic effectiveness of literary works.